Interim to Permanent Chair: Leaders for Today - Neporcha Cone; Corrie L Davis (Academic Chairpersons Conference Proceedings, 2019)
The work of a department chair is demanding and rewarding. However, when stepping into this role on an interim basis, one is faced with the same responsibilities that a permanent chair must endure. The presenters will share lessons learned from being interim chairs, afterwards providing tips for a successful transition.
Keywords: Interim; Department Chair; Transitioning; Vision; Delegate; Expectations; Evaluation